Cepharanthine Prevents Estrogen Deficiency-Induced Bone Loss by Inhibiting Bone Resorption - Zhou, Chen-he; Meng, Jia-hong; Yang, Yu-te; Hu, Bin; Hong, Jian-qiao; Lv, Zheng-tao; Chen, Kun; Heng, Boon Chin; Jiang, Guang-yao; Zhu, Jian; Cheng, Zhao-hui; Zhang, Wei; et al. (Frontiers in Pharmacology, 2018)
Osteoporosis is a common health problem worldwide caused by an imbalance of bone formation versus bone resorption. However, current therapeutic approaches aimed at enhancing bone formation or suppressing bone resorption still have some limitations. In this study, we demonstrated for the first time that cepharanthine (CEP, derived from Stephania cepharantha Hayata) exerted a protective effect on estrogen deficiency-induced bone loss. This protective effect was confirmed to be achieved through inhibition of bone resorption in vivo, rather than through enhancement of bone formation in vivo. Furthermore, the in vitro study revealed that CEP attenuated receptor activator of nuclear factor κB ligand (RANKL)-induced osteoclast formation, and suppressed bone resorption by impairing the c-Jun N-terminal kinase (JNK) and phosphatidylinositol 3-kinase (PI3K)-AKT signaling pathways. The inhibitory effect of CEP could be partly reversed by treatment with anisomycin (a JNK and p38 agonist) and/or SC79 (an AKT agonist) in vitro. Our results thus indicated that CEP could prevent estrogen deficiency-induced bone loss by inhibiting osteoclastogenesis. Hence, CEP might be a novel therapeutic agent for anti-osteoporosis therapy.